The Association of Sleep Disorders, Obesity and Sleep-Related Hypoxia with Cancer - Brzecka, Anna (Curr Genomics, 2020)
BACKGROUND: Sleep disorders have emerged as potential cancer risk factors. OBJECTIVE: This review discusses the relationships between sleep, obesity, and breathing disorders with concomitant risks of developing cancer. RESULTS: Sleep disorders result in abnormal expression of clock genes, decreased immunity, and melatonin release disruption. Therefore, these disorders may contribute to cancer development. Moreover, in sleep breathing disorder, which is frequently experienced by obese persons, the sufferer experiences intermittent hypoxia that may stimulate cancer cell proliferation. DISCUSSION: During short- or long- duration sleep, sleep-wake rhythm disruption may occur. Insomnia and obstructive sleep apnea increase cancer risks. In short sleepers, an increased risk of stomach cancer, esophageal squamous cell cancer, and breast cancer was observed. Among long sleepers (>9 hours), the risk of some hematologic malignancies is elevated. CONCLUSION: Several factors including insomnia, circadian disruption, obesity, and intermittent hypoxia in obstructive sleep apnea are contributing risk factors for increased risk of several types of cancers. However, further studies are needed to determine the more significant of these risk factors and their interactions.